2019
DOI: 10.1111/eci.13121
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term LPS induces aortic valve thickening in ApoE*3Leiden mice

Abstract: Background Recently, it was shown that 12 weeks of lipopolysaccharide (LPS) administration to nonatherosclerotic mice induced thickening of the aortic heart valve (AV). Whether such effects may also occur even earlier is unknown. As most patients with AV stenosis also have atherosclerosis, we studied the short‐term effect of LPS on the AVs in an atherosclerotic mouse model. Methods ApoE*3Leiden mice, on an atherogenic diet, were injected intraperitoneally with either LPS or phosphate buffered saline (PBS), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 52 publications
(100 reference statements)
2
7
0
Order By: Relevance
“…In both wild-type mice and in the atherosclerotic ApoE*3Leiden mouse model, intraperitoneal LPS induces AV thickening, but not calcification, suggesting a role for systemic inflammation in the early stages of CAVD. 193–195 …”
Section: Ros In the Pathophysiology Of Cavdmentioning
confidence: 99%
“…In both wild-type mice and in the atherosclerotic ApoE*3Leiden mouse model, intraperitoneal LPS induces AV thickening, but not calcification, suggesting a role for systemic inflammation in the early stages of CAVD. 193–195 …”
Section: Ros In the Pathophysiology Of Cavdmentioning
confidence: 99%
“…High level of serum lipids and the inflammatory status are risk factors of AS [2,28]. Feeding ApoE -/mice with HFD can induce AS and LPS injection can accelerate the progression of disease [29]. In our study, HFD companied with LPS induced dysfunction of serum lipids and formation of atherosclerotic plaque.…”
Section: Discussionmentioning
confidence: 48%
“…Hyperlipidaemic APOE*3Leiden.CETP transgenic mice not only develop spontaneous atherosclerosis but can also be used for induction of lesions in the aortic valve with similarities to changes observed in human CAVS (van Broekhoven et al, 2019). After 16 weeks of treatment with nilotinib (30 mg·kg −1 ), APOE*3Leiden.CETP transgenic mice developed a significant 1.2‐fold (95% CI 1.059–1.355) increase in valve thickness compared with control mice, and a similar significant increase compared with the imatinib group (Figure 1a).…”
Section: Resultsmentioning
confidence: 99%
“…Aortic valve thickening in hyperlipidaemic mice represents a model of early valvular changes with similar characteristics to human disease in terms of osteogenic activation (Aikawa et al, 2007) and valvular iron (Laguna‐Fernandez et al, 2016; van Broekhoven et al, 2019). The present study revealed that nilotinib, but not imatinib, significantly increased murine valve thickness in hyperlipidaemic APOE*3Leiden.CETP transgenic mice that have a humanized lipoprotein metabolism and exhibit aortic valve thickening at a young age (van Broekhoven et al, 2019), which represents a model of early valvular changes with similar characteristics to human CAVS disease in terms of osteogenic activation (Aikawa et al, 2007), detected through BMP2 stainings in the present study, and valvular iron (Laguna‐Fernandez et al, 2016; van Broekhoven et al, 2019). Interestingly, nilotinib‐treated mice also exhibited a higher proportion of valvular iron positivity, which has been shown to precede calcification in human stenotic aortic valves (Morvan et al, 2019).…”
Section: Discussionmentioning
confidence: 99%